Leading With Callings: Effects of Leader’s Calling on Followers’ Team Commitment, Voice Behavior, and Job Performance - Park, Jiyoung; Lee, Kyoungsu; Lim, Jung In; Sohn, Young Woo (Frontiers in Psychology, 2018)
Viewing work as a calling has been considered to be beneficial to individuals and organizations. However, research to date has largely focused on the effects of individuals’ own callings on themselves, leaving the effects of one’s calling on others unexplored. Based on research that demonstrates prevalent effects of callings and leader’s influences on followers at work, we assumed that leader calling might have positive effects on followers’ outcomes. Specifically, we hypothesized that the extent to which leaders view their work as a calling have positive influences on followers’ team commitment, leader-rated voice behavior, and job performance. We also examined a mediating effect of transformational leadership on the relations between leader’s calling and the three follower’s outcomes. Using data on 284 leader-follower pairs from the South Korean Air Force, we found that leader’s calling was positively associated with followers’ team commitment, voice behaviors, and job performance. The effects of leader’s calling on follower commitment and voice behavior were partly accounted for by follower perceptions of transformational leadership. However, a mediating role of transformational leadership on the link between leader’s calling and job performance was not supported. The implications of these findings are discussed.